Scientific research in economics and management in the thesis - Данилюк, М. О.; Коцкулич, Т. Я. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
1